Thanatology in protoplanetary discs: The combined influence of Ohmic, Hall, and ambipolar diffusion on dead zones - Lesur, Geoffroy; Kunz, Matthew W.; Fromang, Sébastien (Astronomy and astrophysics (Berlin), 2014)
Protoplanetary discs are poorly ionised due to their low temperatures and high column densities and are therefore subject to three "non-ideal" magnetohydrodynamic (MHD) effects: Ohmic dissipation, ambipolar diffusion, and the Hall effect. The existence of magnetically driven turbulence in these discs has been a central question since the discovery of the magnetorotational instability (MRI). Recent work has suggested that a combination of Ohmic dissipation and ambipolar diffusion can render both the midplane and surface layers of the disc inactive and that torques due to magnetically driven outflows are required to explain the observed accretion rates. We reassess this picture by performing three-dimensional numerical simulations that include all three non-ideal MHD effects for the first time. The results demonstrate that if the MRI is relevant for driving mass accretion in protoplanetary discs, one must include the Hall effect to obtain even qualitatively correct results.